Efficacy and Tolerance of Post-operative Hypo-Fractionated Stereotactic Radiotherapy in a Large Series of Patients With Brain Metastases - Martinage, Geoffrey; Geffrelot, Julien; Stefan, Dinu; Bogart, Emilie; Rault, Erwan; Reyns, Nicolas; Emery, Evelyne; Makhloufi-Martinage, Samira; Mouttet-Audouard, Raphaelle; Basson, Laurent; Mirabel, Xavier; Lartigau, Eric; et al. (Frontiers in Oncology, 2019)
Purpose: The aim of this study was to assess, in a large series, the efficacy and tolerance of post-operative adjuvant hypofractionated stereotactic radiation therapy (HFSRT) for brain metastases (BMs). Methods and materials: Between July 2012 and January 2017, 160 patients from 2 centers were operated for BM and treated by HFSRT. Patients had between 1-3 BMs, no brainstem lesions or carcinomatous meningitis. The primary endpoint was local control. Secondary endpoints were distant brain control, overall survival (OS) and tolerance to HFSRT. Results: 73 patients (46%) presented with non-small cell lung cancer (NSCLC), 23 (14%) had melanoma and 21 (13%) breast cancer. Median age was 58 years (range, 22-83 years). BMs were synchronous in 50% of the cases. The most frequent prescription regimens were 24 Gy in 3 fractions (n=52, 33%) and 30 Gy in 5 fractions (n=37, 23%). Local control rates at 1 year and 2 years were 88% [95%CI, 81%-93%] and 81% [95%CI, 70%-88%], respectively. Distant control rate at 1 year was 48% [95%CI, 81%-93%]. In multivariate analysis, primary NSCLC was associated with a significant reduction in the risk of death compared to other primary sites (HR=0.57, p=0.007), the number of extra-cerebral metastatic sites (HR=1.26, p=0.003) and planning target volumes (HR=1.15, p=0.012) were associated with a lower OS. There was no prognostic factor of time to local progression. Median OS was 15.2 months [95%CI, 12.0-17.9 months] and the OS rate at 1 year was 58% [95% CI, 50%-65%]. Salvage radiotherapy was administered to 72 patients (45%), of which 49 received new HFSRT. Ten (7%) patients presented late grade 2 and 4 (3%) patients late grade 3 toxicities. Thirteen (8.9%) patients developed radiation necrosis. Conclusions: This large multicenter retrospective study shows that HFSRT allows for good local control of metastasectomy tumor beds and that this technique is well-tolerated by patients.